The Second Death of Concept Albums World-Building and Unification Strategies in the Age of Streaming - Merlini, Mattia (Interdisciplinary Studies in Musicology, 2021)
As the end of the album format is apparently drawing near due to the radical change in music consumption habits motivated by streaming services, artists and genres interested in creating musical works with meanings broader than those of single songs find themselves in a situation worth analysing. Despite all appearances and expectations, I argue that nowadays artists willing to create narrative, thematic or generally conceptual contexts for their songs are living in a potential second golden age of concept albums. Some attempts at keeping the (concept) album alive are more alike to an act of resistance, others creatively take advantage of the same means of communication used by their digital enemy, in order to create something unique and capable of taking the place of the supposedly doomed CD/lP format. They are often transmedial works, thus requiring an interdisciplinary analysis. In this paper, I offer an overview of the contemporary situation of the album format (and concept album more specifically) and finally propose a classification of four forms of contemporary musical world-building strategies, starting from a selection of emblematic case studies.